2011
DOI: 10.1111/j.1744-6155.2011.00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with emotional response of parents at the time of diagnosis of Down syndrome

Abstract: By providing positive information, healthcare providers can help parents to develop a more optimistic outlook on their children's future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
14

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(54 citation statements)
references
References 19 publications
2
38
0
14
Order By: Relevance
“…Also, diagnostic uncertainty can lead to long-term negative psycho-emotional burden for parents (Lenhard et al 2005). However, parents with a definitive diagnosis can experience similar emotions to parents of non-affected children, possibly because DS is a common genetic condition with a fairly good prognosis (Choi et al 2011;Devlin and Morrison, 2004;Lenhard et al 2005). Early diagnosis can also reduce misdiagnoses and provision of incorrect information by HCPs (Poehlmann et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, diagnostic uncertainty can lead to long-term negative psycho-emotional burden for parents (Lenhard et al 2005). However, parents with a definitive diagnosis can experience similar emotions to parents of non-affected children, possibly because DS is a common genetic condition with a fairly good prognosis (Choi et al 2011;Devlin and Morrison, 2004;Lenhard et al 2005). Early diagnosis can also reduce misdiagnoses and provision of incorrect information by HCPs (Poehlmann et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Upon their child's diagnosis, parents should be given information about symptoms and health complications of DS so that they can recognise and understand these features and seek appropriate support and treatment where necessary for the optimal well-being of the child (Skotko et al 2009). Such information provision could be improved by ensuring HCPs in Pakistan are trained with up to date, accurate knowledge of DS and are able to communicate this in a sensitive manner, where parents can understand the implications for their child (Choi et al 2011;Ferguson et al 2006;Skotko et al 2009). There are challenges in providing information about DS because of the variability of the symptoms and severity of the condition.…”
Section: Discussionmentioning
confidence: 99%
“…These were assessed with eight items on health‐care providers' attitude and content of information for diagnosis, score on a four‐point Likert scale . Higher scores indicate higher support.…”
Section: Methodsmentioning
confidence: 99%
“…In Korea, this is considered as family responsibility, which means that family is responsible for additional needs related to care for them. 27 Korean mothers of children born with Down syndrome experienced any difficulties in caring for their children. 27 Respondents agree to spend a lot of time to assist their children in learning (for example: speaking, writing, reading, etc).…”
Section: Resultsmentioning
confidence: 99%
“…27 Korean mothers of children born with Down syndrome experienced any difficulties in caring for their children. 27 Respondents agree to spend a lot of time to assist their children in learning (for example: speaking, writing, reading, etc). In a qualitative study, it had been found that there was a Chinese mother trying to increase learning potential of her child that born with Down syndrome, as her child experienced delay in learning.…”
Section: Resultsmentioning
confidence: 99%